Application of next-generation sequencing on diagnosis of bloodstream infection caused by Mycoplasma hominis in a patient with ANCA-associated vasculitis - Yili Chen; Hengxin Chen; Hao Huang; Yinyin Zhong; Xiaoshu Lin; Peisong Chen; Kang Liao; Juhua Yang; Min Liu; Mengzhi Hong; Ruizhi Wang (BMC, 2023)
Abstract Background Mycoplasma hominis is one of the main opportunistic pathogenic mycoplasmas in humans which has a major impact on patients with bloodstream infections. Because it is difficult to detect or isolate, rapid and accurate diagnosis using improved methods is essential and still challenging for patients with bloodstream infection. Case presentation In this case, we reported the application of next -generation sequencing for the diagnosis of bloodstream infection caused by Mycoplasma hominis in a patient with Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis. After 9 days of combined treatment with levofloxacin, polymyxin B and meropenem, the patient's condition was gradually controlled and he was discharged without further complications. During the three-month outpatient follow-up, no recurrence of symptoms or clinical signs was reported. Conclusions This successful application of next generation sequencing assisted the rapid diagnosis of Mycoplasma hominis bloodstream infection, provided a new perspective in the clinical approach and highlighted the potential of this technique in rapid etiological diagnosis.